(untitled) (Journal of Dhaka Medical College, 2023)
Introduction: A cross-sectional prospective clinical study was done to evaluate the inner ear anomalies in candidates undergoing cochlear implantation. Materials and Methods: Study was carried out over a period of 07 years (Jan 2013 to Dec 2019) at Cochlear Implant Centre, Combined Military Hospital Dhaka. A total 206 deaf candidates, both pre and post lingual, were included in convenient sampling method. Result: The sample consisted of 206 candidates, of whom 117 (56.80%) were female and 89 (43.20%) were male. All candidates had severe to profound bilateral deafness. 182 (88.35%) of them were pre and 24 (11.65%) were in post lingual group. All patients diagnosed audiologically as profound deafness underwent HRCT scan of temporal bone with 3D reconstruction of cochlea and MRI of internal auditory canal & brain. Radiological examination revealed that 36 (17.47%) candidates had ear anomalies. Mondini deformity 14 (06.80%), cochlear ossification 11 (5.34%), large vestibular aqueduct 04 (1.94%), high jugular bulb 04 (1.94%) and anteriorly placed sigmoid sinus 03 (1.45%) were noted. During intervention, 42 (20.39%) candidates had anomalous intra operative findings. Among them CSF gusher 19 (9.23%), ossification of basal turn 12 (5.83%), isolated rotated Cochlea 02 (0.97%), high jugular bulb 04 (1.94%), anteriorly placed sigmoid sinus 03 (1.45%), and very high facial nerve 02 (0.97%) were observed. During surgery, electrode insertion difficulty due to high CSF gusher was experienced in19 (9.23%) cases, full length of electrode insertion was not possible due to ossified basal turn 12 (5.83%), difficult to find out round window membrane due to rotated cochlea 02 (0.97%), prevented direct visualization of the round window due to high jugular bulb 04 (1.94%), difficult to approach round window due to very high facial nerve 02 (0.97%). and approach to round window membrane was compromised due to anteriorly placed sigmoid sinus 03 (1.45%). Most of these difficulties were effectively managed during surgery. Conclusions: This study highlights the importance of preoperative radiological scanning in the assessment of patients undergoing cochlear implantation. It provides vital information on cochlear status and in ruling out non cochlear causes where cochlear implantation is not feasible. Detection of anatomical abnormalities with appropriate evaluation, specially imaging should be mandatory in every patient undergoing cochlear implantation. J Dhaka Med Coll. 2021; 30(2) : 167-175